Choroba przewlekła jako przeszkoda w osiąganiu niezależności u dzieci - Konieczna, Iwona (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
Chronic diseases determine children’s functioning in different areas of their life. It is caused very often by unclear experiences which are result of typical disease unit (such as physical pain, activity restriction), impact into environment (feeling of danger, fear, physical suffering).Very important seems to be here unit’s activity which play main role in coping process1. Because of many experiences child gain knowledge referring to concrete events strictly connected to therapy process. Basing on this child have a possibility to choose proven strategies which are foundation to effective coping with disease and give possibility to gain wellbeing, efficiency, independence which lead to effective development.